Tijdschrift voor Interieurgeschiedenis en design : Vrouwen en design in België - Serulus, Katarina; Sterckx, Marjan; Bergmans, Anna; Baarsen, Reiner; Gimeno-Martinez, Javier (Leuven : Peeters, 2023)
Guillissen-Hoa, Simone ; des Cressonnères, Josine ; Mme D'Aubreby Van Swae ; Elwes, Mabel Eleanor ; Van Celst-Emonts, Jeanne ; Jasinska, Marcelle ; Lauwaert, Yvette ; Behaeghel, Jeanine ; Bataille, Claire ; Meirens, Jenny ; Loppa, Linda
boek